CYTOTOXICITY OF HEXAVALENT CHROMATE COMPOUNDS IN CH310T1/2 CELLS AND CYTOMODULATION BY SODIUM ARSENITE AND METHANOL EXTRACT OF Rauvolfia vomitora (Afzel) IN MICE. (2015)
Exposure to certain hexavalent chromate compounds (HCC) causes lung and colon cancers. Their mechanisms of cytotoxicity are unclear, but believed to be affected by ascorbate and particle size. However, their role is not clearly defined. Co-exposure with sodium arsenite (SA) is common, but its effect on HCC toxicity is unknown. Current therapy has side effects, necessitating the search for antidote from unexplored natural products such as Rauvolfia vomitora (RV). This study therefore investigates the effect of particle size and ascorbate on cytotoxity of selected HCC [lead chromate (PbCrO4), barium chromate (BaCrO4), strontium chromate (SrCrO4) and potassium dichromate (K2Cr2O7)] in C3H10T1/2 cells and cytomodulatory effects of SA and RV in mice. The effect of ascorbate, dehydroascorbate and particle size on HCC cytotoxicity in C3H10T1/2 cells was determined by measuring survival fraction and yield of foci by microscopy. Actin and cellular ultrastructure disruption and induction of cell death were assessed by electron and fluorescent microscopy. The molecular mechanisms of cytotoxicity and transformation were evaluated in eighty-four cell death genes using real time (RT2) gene array, while cell cycle analysis was done by flow cytometry. Leaves of RV were air dried, powdered and extracted with methanol. Forty male mice (20-25g) were divided into 8 groups of 5 Swiss albino mice each and treated with water (control), RV (275 mg/Kg), SA (2.5 mg/kg), K2Cr2O7 (12 mg/Kg), SA + K2Cr2O7, RV + SA, RV + K2Cr2O7, RV + SA + K2Cr2O7. Rauvolfia vomitora was given orally for seven days, while K2Cr2O7 and SA were administered on day seven. Serum aspartate and alanine aminotransferases (AST and ALT), catalase, glutathione-S-transferase (GST), glutathione and malondialdehyde (MDA) levels were determined by spectrophotometry. Micronucleated polychromatic erythrocytes (mPCEs) were evaluated by microscopy. Data were analysed using ANOVA and Student‟s t- test at p= 0.05. Survival fraction of control cells was 1.0, treatment with PbCrO4 and ≤ 12.5 μM ascorbate or ≤ 2 μM dehydroascorbate decreased it to 0.4. The 15-20 μM ascorbate and 3-4 μM dehydroascorbate reversed it to 0.7. Exposure of cells to small (≤ 3 μm) and large particles (≤ 8 μm) of PbCrO4, BaCrO4 and SrCrO4 resulted in a dose-dependent decrease in survival. The total foci were higher for PbCrO4 (3.8) with large particles and BaCrO4 (6.6) with small particles. Phagocytosis of particles was time-dependent. The HCC treatment led to G2/M and S phase arrest, anucleation, actin disruption and mixed cell death. Thirty-four cell death genes including Bax and Casp3 were up-regulated by 4 folds and six including Bcl-2 and Traf2 were down- regulated in treated cells. Twenty-one anti-apoptotic and autophagy genes including Atg5 and Bcl-2 were up-regulated in PbCrO4 transformed cells. The K2Cr2O7 and/ or SA significantly increased mPCEs, AST, ALT, catalase and MDA levels while glutathione and GST were reduced. The RV restored the markers towards normal values. Cytotoxicty of chromate compounds is particle size and ascorbate dependent. The cytotoxicity might be due to actin disruption, micronuclei induction and cell cycle arrest. Methanol extract of Rauvolfia vomitora modulated the toxicity in mice. Keywords: Hexavalent chromate compounds, Sodium arsenite, Rauvolfia vomitora, Cytotoxicity Word counts: 494